2020
DOI: 10.5187/jast.2020.62.5.753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carcass weight increase on meat quality and sensory properties of pork loin

Abstract: The objective of this study was to investigate the influence of increasing carcass weight (CW) on meat quality traits including meat color, water-holding capacity (WHC), tenderness, backfat thickness and intramuscular fat (IMF) content of pork loin. A total of 96 pork carcasses (48 LYD [Landrace × Yorkshire × Duroc] barrows and gilts) were selected at a commercial slaughterhouse. Each gender had commercial CW (≤ 90 kg), heavy CW (91-100 kg) and very heavy CW (> 100 kg) (16 carcasses from each CW group). Loin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
(56 reference statements)
1
9
1
Order By: Relevance
“…Our findings corroborate those of Hwang et al [ 39 ], who discovered that when pigs’ pre-slaughter weight increased, meat color intensity and taste sensitivity increased dramatically ( p < 0.05), while softness reduced significantly ( p < 0.001). Pre-slaughter weight correlated positively with flavor but negatively with softness, as we also discovered in our trial.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings corroborate those of Hwang et al [ 39 ], who discovered that when pigs’ pre-slaughter weight increased, meat color intensity and taste sensitivity increased dramatically ( p < 0.05), while softness reduced significantly ( p < 0.001). Pre-slaughter weight correlated positively with flavor but negatively with softness, as we also discovered in our trial.…”
Section: Discussionsupporting
confidence: 92%
“…The IMF content of LM in the present study was neither influenced by SW, with an overall average of 2.0%, nor was correlated with the sensory attributes associated with eating quality, which was consistent with the results of Jeong et al [ 8 ] for the lean pigs reared on the low-energy diet with their SW and overall average IMF content being 110–138 kg and 2.6%, respectively. In contrast, Hwang et al [ 44 ] have reported that the IMF content of LM of market pigs increased approximately from 2.1% to 3.0% between their carcass weights below 90 kg and over 100 kg, respectively, which were comparable to those for the Av and XHi groups of the present study, respectively, and that the IMF content was positively correlated with flavor and palatability of cooked LM. Furthermore, Hoa et al.…”
Section: Discussioncontrasting
confidence: 76%
“…IMF content is one of the polygenic traits in animals and is an important determinant of meat quality. Increasing the accumulation of intramuscular fat can promote the formation of meat marble patterns and improve the taste, flavor, color, and other characteristics of meat [ 2 , 3 , 29 , 30 ]. Therefore, in view of the importance of IMF to livestock production economics, it is of great significance to clarify the molecular mechanisms of IMF deposition [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basic screening conditions of transcript information were as follows: (1) we selected the transcripts whose class code was 'i', 'x', 'u', 'o', or 'e'; (2) we selected the transcripts whose length was ≥200 bp with an exon number ≥ 2; and (3) we selected the transcripts with a Fragments per kilobase of exon model per million mapped fragments (FPKM) ≥ 0.1. CPC2 (CPC2-beta) [16], CNCI (v2) [17], and CPAT [18] software were used to predict the coding potential from the basically screened transcripts.…”
Section: Identification Of Lncrnas Mirnas and Circrnamentioning
confidence: 99%
See 1 more Smart Citation